2015
DOI: 10.18632/oncotarget.4762
|View full text |Cite
|
Sign up to set email alerts
|

MiR-497 decreases cisplatin resistance in ovarian cancer cells by targeting mTOR/P70S6K1

Abstract: The mechanism of cisplatin resistance in ovarian cancer is not clearly understood. In the present investigation, we found that the expression levels of miR-497 were reduced in chemotherapy-resistant ovarian cancer cells and tumor tissues due to hypermethylation of miR-497 promoter. Low miR-497 expression levels were associated with chemo-resistant phonotype of ovarian cancer. By analyzing the expression levels of miR-497, mTOR and p70S6K1 in a clinical gene-expression array dataset, we found that mTOR and p70S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 37 publications
2
65
0
Order By: Relevance
“…Our study demonstrated that TXL promoted p70s6k1 expression without changing p70s6k1 mRNA levels, leading us to investigate the role of microRNAs in the anti-apoptotic effects of TXL. Among the three microRNAs (Shi et al, 2012;Xu et al, 2012Xu et al, , 2015) previously reported to target p70s6k1 mRNA and inhibit its translation, only miR-128-3p was downregulated by TXL during I/R. MiR-128-3p was implicated as important in multiple physiological and pathophysiological processes, such as angiogenesis, neuronal plasticity, cholesterol metabolism and differentiation Adlakha and Saini, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study demonstrated that TXL promoted p70s6k1 expression without changing p70s6k1 mRNA levels, leading us to investigate the role of microRNAs in the anti-apoptotic effects of TXL. Among the three microRNAs (Shi et al, 2012;Xu et al, 2012Xu et al, , 2015) previously reported to target p70s6k1 mRNA and inhibit its translation, only miR-128-3p was downregulated by TXL during I/R. MiR-128-3p was implicated as important in multiple physiological and pathophysiological processes, such as angiogenesis, neuronal plasticity, cholesterol metabolism and differentiation Adlakha and Saini, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Because TXL was reported to decrease expression of microRNAs and increase levels of their corresponding proteins under certain conditions (Wang J .Y. et al, 2014;Zhang et al, 2014Zhang et al, , 2017, we used quantitative PCR to examine levels of several microRNAs (Shi et al, 2012;Xu et al, 2012Xu et al, , 2015 The effects of TXL on the protein levels of total p70s6k1 and phosphorylated p70s6k1 in myocardium (n = 4 in each group). *P < 0.05 vs. Sham; # P < 0.05 vs. I/R; $ P < 0.05 vs. I/R+TXL; Ra, rapamycin; TA, total cross-sectional heart area; AAR, area at risk; IA, infract area.…”
Section: Txl Downregulated Mir-128-3p a Microrna Targeting P70s6k1mentioning
confidence: 99%
“…It was reported that the phosphorylation level of mTOR was higher in cisplatin-insensitive clear-cell ovarian carcinoma cells compared with in cisplatin-sensitive cells (12,13). mTOR also performs a key role in the modulation of cisplatin-induced apoptotic cell death.…”
Section: Introductionmentioning
confidence: 99%
“…reported that miRNAs are involved in the regulation of chemoresistance to ovarian cancer, colorectal cancer, non‐small cell lung cancer or breast cancer by targeting mTOR/P70S6K1 and MAP/ERK kinase kinase 1 (MEKK1), among others. In addition, using the targeting miRNAs, they resensitized drug‐resistant cells to anticancer agents .…”
Section: Discussionmentioning
confidence: 99%